2013
DOI: 10.1007/s10592-013-0474-y
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling landscape variables with multiple approaches to overcome scarce species knowledge: a landscape genetic study of the slow worm

Abstract: Landscape genetics was developed to detect landscape elements shaping genetic population structure, including the effects of fragmentation. Multifarious environmental variables can influence gene flow in different ways and expert knowledge is frequently used to construct friction maps. However, the extent of the migration and the movement of single individuals are frequently unknown, especially for non-model species, and friction maps only based on expert knowledge can be misleading. In this study, we used thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
7
0
3
Order By: Relevance
“…Although males are more likely to disperse, there is a higher potential that interaction between a male and a random dispersal event from a female may result in recolonization. Previous research on slow-worms has shown that they are capable of travelling large distances and that dispersal events could be under represented (Geiser 2013). The same study also showed that slowworms can migrate over areas that were previously thought to be impassable, further supporting the theory that slow-worms exist in a metapopulation (Geiser 2013).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Although males are more likely to disperse, there is a higher potential that interaction between a male and a random dispersal event from a female may result in recolonization. Previous research on slow-worms has shown that they are capable of travelling large distances and that dispersal events could be under represented (Geiser 2013). The same study also showed that slowworms can migrate over areas that were previously thought to be impassable, further supporting the theory that slow-worms exist in a metapopulation (Geiser 2013).…”
Section: Discussionmentioning
confidence: 56%
“…Previous research on slow-worms has shown that they are capable of travelling large distances and that dispersal events could be under represented (Geiser 2013). The same study also showed that slowworms can migrate over areas that were previously thought to be impassable, further supporting the theory that slow-worms exist in a metapopulation (Geiser 2013). For future conservation of the slow-worm, creating dispersal channels to promote a larger network of subpopulations would encourage recolonization and reduce the decline in British populations.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The terms slow worm, and especially blind worm, are misnomers: Anguis fragilis is neither a worm nor is it blind (Petzold, 1971;Böhme, 1981;Völkl and Alfermann, 2007;Geiser et al, 2013). It is in fact a legless lizard of some 40 cm in length, with a wide distribution centered in the temperate climate zone of Europe (German: Blindschleiche; French: orvet; Italian: orbetto; Spanish: culebra de cristal).…”
mentioning
confidence: 99%